GANGGUAN BERBAHASA PADA ANAK USIA 7 TAHUN - Lutfiyani, Maudina Dina (Universitas Islam Sumatera Utara, 2023)
Language cannot be separated from human life. Interaction is something that occurs in social activities between individuals, using language intermediaries as media. Language is a sound symbol system that is arbitrary and meaningful, used by the community or a group as a means of communication. The language that is spoken by each individual sometimes gets interference, when acquiring language with unclear pronunciation of words. This research is related to language disorders in children aged 7 years, (psycholinguistic study) with the aim of identifying language disorders and their causes. The method used in this research is descriptive qualitative. The data were obtained by using the technique of listening to interviews. The results of the research were obtained in the form of language disorders namely, lisp (lipsing), pelo (slurring) and the release of the phoneme money due to internal and external reasons.